Practitioner Review: Evidence‐based practice guidelines on alcohol and drug misuse among adolescents: a systematic review. (7th October 2013) - Bekkering, G.E.; Aertgeerts, B.; Asueta‐Lorente, J.‐F.; Autrique, M.; Goossens, M.; Smets, K.; van, J.C.H.; Vanderplasschen, W.; Van, P.; Hannes, K.; ,
<x xml:space="preserve">Abstract</x> Background Context‐specific evidence‐based guidelines on how to prevent and treat substance misuse among adolescents are currently lacking in many countries. Due to the time consuming nature of de novo guideline development, the ADAPTE collaboration introduced a methodology to adapt existing guidelines to a local context. An important step in this method is a systematic review to identify relevant high‐quality evidence‐based guidelines. This study describes the results of this step for the development of guidelines on adolescent alcohol and drug misuse in Belgium. Methods Rigorous systematic review methodology was used. This included searches of electronic databases (Medline, Embase, Cinahl, PsychInfo, and ERIC in June 2011), websites of relevant organizations, and reference lists of key publications. Experts in the field were also contacted. Included were Dutch, English, French, or German evidence‐based practice guidelines from 2006 or later on the prevention, screening, assessment, or treatment of alcohol or illicit drug misuse in persons aged 12–18 years. Two independent reviewers assessed the quality of the guidelines using the AGREE II (Appraisal of Guidelines for Research and Evaluation) instrument. Scope This overview provides a framework of current knowledge in adolescent alcohol and drug misuse prevention and treatment. Results This systematic review identified 32 relevant evidence‐based guidelines on substance misuse among adolescents. Nine guidelines were judged to be of high quality; of which four had recommendations specifically on adolescents: one on school‐based prevention, one on substance misuse prevention in vulnerable young people and two on alcohol misuse with specific sections for the adolescent population. There were few commonalities as guidelines focused on different target groups, professional disciplines and type and level of substance misuse. Evidence to support the recommendations was sparse, and many recommendations were based on expert consensus or on studies among adults. Also, the link between evidence and recommendations was often unclear. Conclusions There are a substantial number of guidelines addressing substance misuse in adolescents. However, only four high‐quality guidelines included recommendations specific for adolescents. The current level of evidence that underpins the recommendations in these high‐quality guidelines is low.